Association between dietary zinc intake and epilepsy: findings from NHANES 2013–2018 and a Mendelian randomization study - Huang, Shicun; Gao, Ya; Chen, Yingqi; Wang, Yiqing; Lu, Yeting; Gao, Wei; Hu, Xiaowei; Fang, Qi (Frontiers in Nutrition, 2024)
Background: The association between dietary zinc intake and epilepsy remains unclear.This study aimed to investigate the relationship between zinc intake from the diet and epilepsy, employing Mendelian randomization (MR) to explore potential causal links between zinc and epilepsy.Methods: The cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2013 and 2018. Among the 4,434 participants included, 1.5% (67/4,434) reported having epilepsy. Restricted cubic spline models and logistic regression models were employed to examine the relationships between dietary zinc intakes and epilepsy. Subsequently, a 2-sample Mendelian randomization (MR) analysis was conducted using the inverse variance weighted (IVW) approach as the primary analysis.Results: In the restricted cubic spline (RCS) analysis, the relationship between dietary zinc consumption and epilepsy displayed an L-shaped curve (nonlinear, p = 0.049).After multivariate adjustments，the adjusted odds ratios for epilepsy in T2 (5.0-11.0 mg/day) and T3 (≥11.0 mg/day) were 0.49 (95% confidence interval [CI]: 0.26-0.92, p = 0.026) and 0.60 (95% CI: 0.31-1.17, p = 0.132), respectively, compared to the lowest dietary zinc consumption tertile (T1, ≤5.0 mg/day). The IVW method indicated that genetically predicted zinc intake per standard-deviation increase was inversely associated with three types of epilepsy, including all types of epilepsy (OR = 1.06, 95% CI: 1.02-1.11, P= 0.008), generalized epilepsy (OR = 1.13, 95% CI: 1.01-1.25, P= 0.030), and focal epilepsy (documented hippocampal sclerosis) (OR = 1.01, 95% CI:1.00-1.02, P= 0.025). Conclusion: Our findings suggest that a daily zinc intake ranging from 5.0 to 11.0 mg is associated with the lowest risk of epilepsy. Furthermore, Mendelian randomization (MR) studies provide additional support for the existence of a causal relationship between zinc and epilepsy.